Photocatalyst design based on two-dimensional materials. (March 2019) - Li, Y.; Gao, C.; Long, R.; Xiong, Y.
Abstract: Benefiting from large specific area and excellent charge transfer performance, two-dimensional (2D) materials exhibit inspiring performance in photocatalytic H2 evolution, CO2 conversion, N2 fixation, and other applications. Aiming to illustrate how to seek and modify 2D materials toward specific applications, here we present a review on photocatalyst design based on 2D materials. This review article starts with a brief introduction to the strength and weakness of regular 2D material–based photocatalysts, followed by a summary on the 2D materials commonly used in photocatalysis and their synthetic approaches. As the central part of this review, multifarious strategies for maneuvering the performance of 2D material–based photocatalysts are then outlined. Finally, we discuss the challenges and opportunities for further development on 2D material–based photocatalysts toward energy and environmental applications based on the recent progress from the angle of surface science and coordination chemistry. Graphical abstract: This review article summarizes the recent advances in the photocatalyst design based on 2D materials. The strength and weakness of regular two-dimensional (2D) material–based photocatalysts as well as the 2D materials commonly used in photocatalysis are outlined, along with multifarious strategies for maneuvering their performance.Image 1 Highlights: This review article summarizes the recent advances in the photocatalyst design based on two-dimensional (2D) materials. The strength and weakness of regular 2D material–based photocatalysts are overviewed. The 2D materials commonly used in photocatalysis and their synthetic approaches are summarized. Multifarious strategies for maneuvering the performance of 2D material–based photocatalysts are outlined. The opportunities for further development of 2D photocatalysts toward energy and environmental applications are highlighted.